Prevalence and factors associated with food insecurity in indigenous families in the state of Alagoas (Northeast Brazil): a population-based cross-sectional study - Almeida, Elison Ruan da Silva; Santos, Tamara Rodrigues dos; Fávaro, Thatiana Regina; Santos, Ewerton Amorim dos; Assunção, Monica Lopes de; Ferreira, Haroldo da Silva (Frontiers in Public Health, 2025)
BackgroundDespite recent efforts by the government to combat Food Insecurity (FI), this issue remains a significant problem in Brazil, particularly among populations experiencing social vulnerability, such as Indigenous peoples. This study aimed to assess the prevalence and factors associated with FI in Indigenous families in the state of Alagoas.MethodIt was a population-based cross-sectional survey using a probabilistic sample (n = 1270 families) representing the 11 ethnic groups present in the state. FI was defined according to the Brazilian Food Insecurity Scale. Factors associated with moderate and severe FI were determined through multivariable analysis using Poisson regression with robust variance adjustment (prevalence ratio – PR and 95% CI).ResultsThe prevalence of FI was 69.1% (39.6, 23.2, and 6.3% in mild, moderate, and severe forms, respectively). Factors associated (p < 0.05) with moderate and severe FI included: female-headed households; houses made of mud or wood; with ≤4 rooms; head of the household with ≤8 years of schooling; retired or unemployed household head; and total family income <2 National Minimum Wages.ConclusionThe prevalence of FI among Alagoas Indigenous peoples is considerably high and associated with poorer demographic, socioeconomic, and environmental conditions, highlighting the social inequities they face and emphasizing the need for intersectoral public policies to address this scenario.